2019
DOI: 10.15835/nbha47311394
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mineral and Vitamin C Contents in Different Parts of Beetroots (Beta vulgaris L.)

Abstract: Due to the increasing popularity of today’s health-conscious culture, beetroot plays an increasingly important role in a healthy, varied diet. While it contains vitamins B1, B2, B6, P, as well as high levels of vitamin C, several studies have proven its role in the prevention of many cancers. The aim of this study was to compare morphological properties, dry matter, and vitamin C and minerals contents in the different parts (peel, end, middle and top part of root) of the three investigated beetroot cultivars g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…It participates in the functioning of the nervous system, blood clotting processes, cholesterol digestion, and it is a component of the skeleton [ 11 ]. Beta vulgaris L. also contains Fe, which is a component of many enzymes, but it is also part of the haem that forms the prosthetic groups of haemoglobin [ 12 ]. It takes part in the synthesis of hormones (such as serotonin, prostaglandins, thyroxine, and triiodothyronine), affects cholesterol metabolism, and promotes detoxification [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It participates in the functioning of the nervous system, blood clotting processes, cholesterol digestion, and it is a component of the skeleton [ 11 ]. Beta vulgaris L. also contains Fe, which is a component of many enzymes, but it is also part of the haem that forms the prosthetic groups of haemoglobin [ 12 ]. It takes part in the synthesis of hormones (such as serotonin, prostaglandins, thyroxine, and triiodothyronine), affects cholesterol metabolism, and promotes detoxification [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This disparity could be due to a variety of factors such as soil acidity as acidic soils are more likely to cause nutrient deficiencies in beetroot (25). Peeling and application of fertilizer can also affect the iron content as it has been shown that the peels of beetroot and beetroots treated with fertilizer contain more iron than other parts of beetroot (26). Zinc is involved in the regulation of the cardiovascular and reproductive system, and the wound healing process (27).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is involved in the regulation of the cardiovascular and reproductive system, and the wound healing process (27). Iron is a component of many enzymes that takes part in hormone and DNA synthesis (26,28), cholesterol metabolism, detoxification, and immune function (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A reversed phase C18 column (Supelco, 250 p 4.6 mm i.d., 5 mm) was used for the analysis. To record the chromatograms, the required time, injected volume, and flow rate of 5 min, 20 mL and 1.5 mL min À1 were adopted, respectively (Székely et al, 2019). Five parallel measurements were performed during the study.…”
Section: Methodsmentioning
confidence: 99%